Healthy Life Centres: a 3-month behaviour change programme’s impact on participants’ physical activity levels, aerobic fitness and obesity: an observational study - Ellen Eimhjellen Blom; Eivind Aadland; Ane Kristiansen Solbraa; Line Merethe Oldervoll (BMJ Open)
Objectives Individuals with low socioeconomic status and multimorbidity tend to have lower physical activity (PA) levels than the general population. Primary care is an important setting for reaching high-risk individuals to support behaviour change. This study aimed to investigate the impact of behaviour change interventions delivered by Norwegian Healthy Life Centres (HLCs) on participants’ PA levels, aerobic fitness and obesity, and furthermore to investigate possible predictors of change.Design An observational study with a pre–post design and a 3-month follow-up.Setting Thirty-two HLCs in Norway were included.Participants A total of 713 participants (72% of the participants included at baseline), 71% women, with a mean age of 51 (18–87 years) and body mass index (BMI) of 32 (SD 7) met to follow-up.Intervention Individual consultations and tailored individual and group-based exercise and courses organised by the HLCs and cooperating providers.Outcome measures The primary outcome was time spent in moderate to vigorous PA (MVPA, min/day) (ActiGraph GT3X+ accelerometer). The secondary outcomes were light PA (LPA, min/day), number of steps per day, time spent sedentary (SED, min/day), aerobic fitness (submaximal treadmill test, min), BMI (kg/m2) and waist circumference (WC, cm).Results There was no change in MVPA (B 1.4, 95% CI −0.4 to 3.1) after 3 months. The participants had improved LPA (4.0, 95% CI 0.5 to 7.5), increased number of steps (362, 95% CI 172 to 552), reduced SED (−5.6, 95% CI −9.8 to –1.3), improved fitness (0.8, 95% CI 0.6 to 1.0), reduced BMI (−0.2, 95% CI −0.1 to –0.3) and reduced WC (−1.7, 95% CI −2.0 to –1.3). Positive predictors of change were number of exercise sessions completed per week, duration of adherence to HLC offers and participation in exercise organised by HLC.Conclusion Participation in the HLC interventions had small positive impacts on participants’ PA levels, aerobic fitness and obesity. Further research to develop effective behaviour change programmes targeting individuals with complex health challenges is needed.Trial registration number NCT03026296.